Mindfulness training supported by a restorative natural setting: Integrating individual and environmental approaches to the management of adaptive resources - Restoration skills training (ReST) in a natural setting compared to conventional mindfulness training: Sustained advantages at a 6-month follow-up - Lymeus, Freddie; Hartig, Terry; Lindberg, Per (Uppsala University, 2023)
This project integrates restorative environments research and mindfulness research: two disparate but related approaches to managing the demands of modern living. Both offer ways to improve attention regulation by detaching from routine mental contents and engaging with present experience. However, restoration works bottom-up, from supportive environmental features, while mindfulness meditation works top-down, through effortful training. Complementarities between the two are the foundations of restoration skills training (ReST), a five-week mindfulness-based course that uses mindful sensory exploration in a natural setting to build a meditative state effortlessly. As in conventional mindfulness training (CMT), ReST involves a learning structure to teach versatile adaptive skills. Data were collected in four rounds, with successively refined versions of ReST given in a botanic garden and formally matched CMT given indoors. Data were collected to test short-term outcomes of practice sessions and long-term course outcomes.

These data form the basis of the analyses presented in (Lymeus et al. (2022) Mindfulness-based restoration skills training (ReST) in a natural setting compared to conventional mindfulness training: Sustained advantages at a 6-month follow-up. Frontiers in Psychology). Note that some variables (marked T1 and T2) are also available in a related dataset (https://doi.org/10.5878/p34t-9j15) and were used in (Lymeus et al. (2020) Mindfulness-based restoration skills training (ReST) in a natural setting compared to conventional mindfulness training: Psychological functioning after a five-week course. Frontiers in Psychology) and were reused by Lymeus et al. in 2022 as background for the follow-up analyses.
Data were collected before, immediately after, and six months after two different five-week mindfulness training courses: restoration skills training (ReST) and conventional mindfulness training, between which participants were randomly assigned. The participants were university students who experienced stress or concentration problems. The procedure was repeated in four rounds of data collection during which the ReST course was progressively refined. The data set includes only participants who completed any of the courses during data collection rounds 2-4 (N = 97). The dataset includes original data containing some missing values and 30 datasets with multiple imputations containing complete data.
Data were collected with the Five Facet Mindfulness Questionnaire (FFMQ; Baer et al. (2006). Using self-report assessment methods to explore facets of mindfulness. Assessment, 13(1), 27-45.), Cognitive Failures Questionnaire (Broadbent et al. (1982). The Cognitive Failures Questionnaire (CFQ) and its correlates. British Journal of Clinical Psychology, 21(1), 1-16.) and the Perceived Stress Scale (Cohen et al. (1983). A global measure of perceived stress. Journal of Health and Social Behavior, 24(4), 385-396).

Detta projekt integrerar forskning om restorativa miljöer och mindfulnessforskning: två olika men relaterade metoder för att hantera kraven i modernt liv. Båda erbjuder sätt att förbättra uppmärksamhetsregleringen genom att ta ökad distans från rutinmässigt mentalt innehåll och engagera sig i nuvarande erfarenhet. Återhämtning fungerar emellertid bottom-up, med hjälp av miljöns stödjande egenskaper, medan mindfulnessmeditation fungerar top-down, genom ansträngande träning. Komplementariteter mellan de två är grunden för restoration skills training (ReST), en fem veckors mindfulness-baserad kurs som använder sensoriskt utforskande i en naturlig miljö för att bygga ett meditativt tillstånd utan ansträngning. Liksom i konventionell mindfulnesstraining har ReST en inlärningsstruktur för att lära ut mångsidiga anpassningsförmågor. Data samlades in i fyra omgångar, med successivt förfinade versioner av ReST som gavs i en botanisk trädgård och formellt matchad konventionell mindfulnessträning inomhus. Data samlades in för att testa för kortsiktiga utfall av enstaka träningspass och för långsiktiga utfall av kurserna.

Dessa data ligger till grund för de analyser som presenteras i (Lymeus et al. (2022) Mindfulness-based restoration skills training (ReST) in a natural setting compared to conventional mindfulness training: Sustained advantages at a 6-month follow-up. Frontiers in Psychology). Observera att vissa variabler (markerade T1 och T2) även finns i ett relaterat dataset (https://doi.org/10.5878/p34t-9j15) och användes i (Lymeus et al. (2020) Mindfulness-based restoration skills training (ReST) in a natural setting compared to conventional mindfulness training: Psychological functioning after a five-week course. Frontiers in Psychology) och återanvändes av Lymeus et al 2022 som bakgrund till uppföljningsanalyserna.
Data samlades in före, direkt efter och sex månader efter två olika femveckors mindfulnesstränings-kurser: restoration skills training (ReST) och konventionell mindfulnessträning, mellan vilka deltagarna fördelades slumpmässigt. Deltagarna var universitetsstudenter som upplevde stress eller koncentrationsproblem. Förfarandet upprepades i fyra datainsamlingsomgångar under vilka ReST-kursen successivt förfinades. Datamaterialet omfattar endast deltagare som genomförde någon av kurserna under datainsamlingsomgångarna 2-4 (N = 97). Datamängden omfattar originaldata som innehåller vissa saknade värden och 30 dataset med multipla imputeringar som innehåller fullständiga data.
Data samlades in med Five Facet Mindfulness Questionnaire (FFMQ; Baer et al. (2006). Using self-report assessment methods to explore facets of mindfulness. Assessment, 13(1), 27–45.), Cognitive Failures Questionnaire (Broadbent et al. (1982). The Cognitive Failures Questionnaire (CFQ) and its correlates. British Journal of Clinical Psychology, 21(1), 1–16.) och Perceived Stress Scale (Cohen et al. (1983). A global measure of perceived stress. Journal of Health and Social Behavior, 24(4), 385–396.)
Träning i medveten närvaro med stöd av en restorativ naturmiljö: Integrering av individbaserade och miljöbaserade metoder för hantering av adaptiva resurser - Mindfulness-baserad träning i återhämtningsfärdigheter (restoration skills training, ReST) i en naturlig miljö jämförd med konventionell mindfulnessträning: Vidmakthållna fördelar vid uppföljning efter sex månader
Keywords: health; hälsa; natural environment; naturmiljö; meditation; meditation; undergraduates; universitetsstuderande på grundnivå; clinical psychology; klinisk psykologi; psychological effects; psykologiska effekter; Restoration; Återhämtning; Mindfulness; Medveten närvaro; Nature; Natur; Training; Träning; Attention; Uppmärksamhet; Health; Hälsa; PSYCHOLOGY; PSYKOLOGI; Psychology; Psykologi